2017
DOI: 10.1371/journal.pgen.1006648
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of A-to-I RNA editing in Drosophila

Abstract: Adenosine-to-inosine (A-to-I) editing is hypothesized to facilitate adaptive evolution by expanding proteomic diversity through an epigenetic approach. However, it is challenging to provide evidences to support this hypothesis at the whole editome level. In this study, we systematically characterized 2,114 A-to-I RNA editing sites in female and male brains of D. melanogaster, and nearly half of these sites had events evolutionarily conserved across Drosophila species. We detected strong signatures of positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 122 publications
5
102
0
Order By: Relevance
“…TE insertions often disrupt CDSs or regulatory sequences [31,40,46]. To explore the impact of TE insertions on the expression levels of the host genes, we examined the whole-body transcriptomes of adult females for 5 GDL strains (B12, I17, N10, T05, and ZW155) [114]. As expected [50,95,115], we found genes with novel TE insertions in exons, especially in CDSs, had significantly reduced expression levels ( Fig.…”
Section: Resultsmentioning
confidence: 60%
“…TE insertions often disrupt CDSs or regulatory sequences [31,40,46]. To explore the impact of TE insertions on the expression levels of the host genes, we examined the whole-body transcriptomes of adult females for 5 GDL strains (B12, I17, N10, T05, and ZW155) [114]. As expected [50,95,115], we found genes with novel TE insertions in exons, especially in CDSs, had significantly reduced expression levels ( Fig.…”
Section: Resultsmentioning
confidence: 60%
“…The ECS is part of the core double-stranded RNA (dsRNA) region required for editing, and is the sequence opposite the editing sites in the secondary structure. We specifically identified how many sites have at least one highly differentiated SNP (top 0.5% Fst) within 100 bases, and how many have at least one differentiated SNP in their respective computationally predicted ECSs 14 , 31 . We found that 3/26 (11.5%) of differentially edited sites between the NFS1 and SFS fly lines are near at least one highly differentiated SNP, whereas 2/378 (5.3%) of non-differentially edited sites are near one ( p -value = 0.0022, one-sided Fisher’s exact test).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, A-to-I editing sites identified in the coding regions are largely deleterious rather than beneficial, as both the frequency and level of nonsynonymous editing events are significantly lower than those of synonymous editing events (11). Recently, it has been reported that the nonsynonymous editing sites in brains and evolutionarily constrained editing sites are generally adaptive in Drosophila (53)(54)(55). In this study, we showed that the nonsynonymous editing events in N. crassa are generally beneficial and favored by positive selection during evolution.…”
Section: Discussionmentioning
confidence: 99%